Implementasi P5 dalam Meningkatkan Jiwa Berwirausaha pada Peserta Didik - Wirayuda, Farhan Iqbal; Rivanti, Firaneta; Asfia, Firda Nur; Salsabila, Natasya Dian; Meisya, Zellia Dini (Indonesian Journal Publisher, 2024)
This research seeks to explain the activities of the Pancasila Student Profile Strengthening Project, the theme of entrepreneurship. This study uses a qualitative approach and descriptive type. The research conducted interviews with the school principal, class IV teachers and several study results showed that the implementation of the project to follow the profile of Pancasila students and the entrepreneurship theme for class 4 of SD N 3 Sendang Agung was carried out well and received a good response from students. P5 activities can develop an entrepreneurial spirit and be friendly with students, but P5 activities must be developed so that the activity time is longer until students feel that business activities are more meaningful. Indonesian students must have great motivation to continue to develop into students of international quality and character with local cultural values. The Pancasila learning profile is a forum for channeling the talents and creativity of elementary school students according to the expertise of each student. Creativity is a complex field of study that gives rise to various trade differences.